Effect of defoliation on production components at different growth stages of cowpea - Smiderle, Oscar; Lima-Primo, Hyanameyka; Barbosa, Haroldo; Souza, Aline (Revista Ciência Agronômica, 2017)
Cowpea (Vigna unguiculata (L.) Walp.) is an important crop for food and  the main source of plant protein for tropical and subtropical regions of the world. The objective of this study was to verify the influence of defoliation levels in three stages of development of cowpea plants cv. ‘BRS Bragança’ on production components. The experiment was carried out at Embrapa Roraima in a greenhouse adopting the completely randomized design with five replications arranged in a factorial scheme 3 x 3. Three phenological stages (trifoliate leaves, flowering, and pod production) and three levels of defoliation (0%; 33% and 67%) were considered. The number of pods per plant (nPPl), number of seeds per pod (nSP), number of seeds per plant (nSPl), mass of seeds per plant (mSPl, g), yield estimate (ePROD, kg ha-1) and mass of one thousand seeds (m1000S, g) were evaluated. The production components of cowpea cv. BRS Bragança varied with the growth stages of the plant and defoliation levels. Defoliation levels do not influence the number of seeds per pod at the three growth stages, although the mass of one thousand seeds is reduced with defoliations of 33 and 67%. Defoliation above 33% at the flowering stage reduces the number of seeds per plant, mass of seeds, and pods per plant, as well as yield estimate. On the other hand, defoliations of 67% reduced the number of pods per plant and seeds per pod at the flowering and pod production stages, respectively.